Colloidally Stable P(DMA-AGME)-Ale-Coated Gd(Tb)F(3):Tb(3+)(Gd(3+)),Yb(3+),Nd(3+) Nanoparticles as a Multimodal Contrast Agent for Down- and Upconversion Luminescence, Magnetic Resonance Imaging, and Computed Tomography - Shapoval, Oleksandr (Nanomaterials (Basel), 2021)
Multimodal imaging, integrating several modalities including down- and up-conversion luminescence, T(1)- and T(2)(T(2)*)-weighted MRI, and CT contrasting in one system, is very promising for improved diagnosis of severe medical disorders. To reach the goal, it is necessary to develop suitable nanoparticles that are highly colloidally stable in biologically relevant media. Here, hydrophilic poly(N,N-dimethylacrylamide-N-acryloylglycine methyl ester)-alendronate-[P(DMA-AGME)-Ale]-coated Gd(Tb)F(3):Tb(3+)(Gd(3+)),Yb(3+),Nd(3+) nanoparticles were synthesized by a coprecipitation method in ethylene glycol (EG) followed by coating with the polymer. The particles were tho-roughly characterized by a dynamic light scattering (DLS), transmission electron microscopy (TEM), Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), X-ray energy dispersive spectroscopy (EDAX), selected area electron diffraction (SAED), elemental ana-lysis and fluorescence spectroscopy. Aqueous particle dispersions exhibited excellent colloidal stability in water and physiological buffers. In vitro toxicity assessments suggested no or only mild toxicity of the surface-engineered Gd(Tb)F(3):Tb(3+)(Gd(3+)),Yb(3+),Nd(3+) particles in a wide range of concentrations. Internalization of the particles by several types of cells, including HeLa, HF, HepG2, and INS, was confirmed by a down- and up-conversion confocal microscopy. Newly developed particles thus proved to be an efficient contrast agent for fluorescence imaging, T(1)- and T(2)(T(2)*)-weighted magnetic resonance imaging (MRI), and computed tomography (CT).